15 Deoxy Δ12,14 PGJ2 Induces Procoagulant Activity in Cultured Human Endothelial Cells - Xie, Shaoping; O’Regan, David J.; Kakkar, Vijay V.; Scully, Michael F. (Thrombosis and Haemostasis, 2002)
15 deoxy Δ12,14 PGJ2 (15d-PGJ2), a high affinity ligand of peroxisome proliferator-activated receptor γ (PPAR γ has been proposed to act as a negative feedback regulator of the inflammatory response. We investigated the effect of 15d-PGJ2 on the anticoagulant property of endothelial cells. 15d-PGJ2 stimulated a moderate but sustained increase in tissue factor (TF) activity in HUVECs and EA.hy926 cells while causing a partial loss of thrombomodulin (TM) activity. When cells were co-treated with 15d-PGJ2 and TNF-α, the subsequent elevation of TF activity was synergistically increased over that of cells treated with TNF-α, alone and the decline of TF activity after 24 h was less marked than TNF-α, alone. The induction of TF by 15d-PGJ2 alone and in combination with TNF-α, was reduced in the presence of PD 98059, suggesting the participation of the MEK/ERK pathway. The thiazolidinedione PPAR γ agonist ciglitazone had no effect on TF levels but reduced the expression of endothelial protein C receptor. The ability of 15d-PGJ2 to enhance a procoagulant phenotype arising from TNF-α, suggests a pro-inflammatory role for the prostaglandin.
Keywords: 15 deoxy Δ12,14 PGJ2; peroxisome proliferator-activated receptor γ; tissue factor; thrombomodulin; endothelial cells